Improving Secondary School Students’ Achievement in Chemistry Through Interaction Pattern Approach - Nwafor, Stephen Chinedu; Ezeanya, Maureen Chinyere; Ameh, Rachael Folake; Muoneke, Nneora Mary (RADINKA JAYA UTAMA PUBLISHER, 2024)
The study determined the effect of interaction pattern approach on secondary students’ achievement in Chemistry. The study was carried out in Awka South Local Government Area of Anambra State. The study employed a quasi-experimental research design. Specifically, the pre-test, post-test non-equivalent control group design was used. A sample size of 112 (45 male & 67 female) out of the 1,522 senior secondary two (SS2) Chemistry students was selected using purposive and simple random sampling techniques. A 50 multiple-choice objective items Chemistry Achievement Test (CAT) developed by the researchers was the instrument used for data collection. The reliability index of 0.92 was obtained for CAT using Kendall’s Coefficient of Concordance (w). Data were analysed mean and standard deviation to answer the research questions and Analysis of Covariance (ANCOVA) to test the hypotheses at 0.05 level of significance. The findings of the study revealed that interaction pattern approach (IPA) significantly improves students’ achievement in Chemistry than the conventional lecture approach (CLA). Gender has no significant influence on students’ achievement in chemistry when taught using IPA. Also, there is no significant interaction effect of instructional approaches and gender on students’ achievement in chemistry. Based on the findings, it was recommended that chemistry teachers should make use of IPA to improve students’ achievement in the subject and promote gender friendly chemistry teaching and learning.